The Parabolic Effect of Managerial Ownership and the Impact Toward Firm’s Performance - Kartika Nuringsih, William Susanto, (Jurnal Ekonomi, 2020)
The purpose of the study is to analyze the impact determinants and the parabolic effect of managerial ownership on a firm’s performance. The model consists of managerial ownership, institutional ownership, family ownership, leverage, asset growth, dividend policy, business risk, and firm size. Purposive sampling is used on non-financial companies in the Indonesian Stock Exchange with a total observation of 539 firm-years. The panel least square is used to analyze the determinants of performance while Panel EGLS is used to analyze the parabolic effect. The study finds that managerial ownership, institutional ownership, dividend policy, and firm size have a positive and significant impact on the firm’s performance. Contrarily, some variables e.g., family ownership, leverage, and asset growth have a negative significant impact on performance. Business risk is not able to prove a significant relationship with performance. Further, the study shows a parabolic effect of managerial ownership, therefore, it proves a model for reducing agency conflict on corporate financial decisions.